Murine Typhus in Travelers Returning from Indonesia - Philippe Parola; Dirk Vogelaers; Chantal Roure; François Janbon; Didier Raoult (Emerging Infectious Diseases, 1998)
We report the first three documented cases of murine typhus imported into Europe from Indonesia, discuss clues for the diagnosis of the disease, and urge that murine fever be considered in the diagnosis of febrile disease in travelers.